2023
DOI: 10.3390/healthcare11182584
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Models in Health Information Exchange: A Systematic Review of Clinical Implications

Sahar Borna,
Michael J. Maniaci,
Clifton R. Haider
et al.

Abstract: Electronic health record (EHR) systems collate patient data, and the integration and standardization of documents through Health Information Exchange (HIE) play a pivotal role in refining patient management. Although the clinical implications of AI in EHR systems have been extensively analyzed, its application in HIE as a crucial source of patient data is less explored. Addressing this gap, our systematic review delves into utilizing AI models in HIE, gauging their predictive prowess and potential limitations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The influence of AI in management extends to treatment planning while presenting a comprehensive and holistic approach. Studies have shown how AI can process datasets including electronic health records, genetic factors and patient preferences (21,22). By incorporating AI into treatment planning prosthodontists are empowered to tailor interventions according to each individual's needs.…”
Section: Managementmentioning
confidence: 99%
“…The influence of AI in management extends to treatment planning while presenting a comprehensive and holistic approach. Studies have shown how AI can process datasets including electronic health records, genetic factors and patient preferences (21,22). By incorporating AI into treatment planning prosthodontists are empowered to tailor interventions according to each individual's needs.…”
Section: Managementmentioning
confidence: 99%